2016
DOI: 10.1007/s13555-016-0148-z
|View full text |Cite
|
Sign up to set email alerts
|

Current and Emerging Medical Therapies for Primary Hyperhidrosis

Abstract: Hyperhidrosis is defined as the production of sweat beyond what is physiologically necessary to maintain thermal homeostasis. This disease state may (and typically does) have a significant impact on the patient’s quality of life. Medications including antiperspirants, anticholinergics, and botulinum toxin have been shown to be effective in the management of hyperhidrosis. Several medical device technologies have also proven to be effective. This review article will explore the current and emerging pharmacologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
55
0
16

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(73 citation statements)
references
References 91 publications
0
55
0
16
Order By: Relevance
“…In primary hyperhidrosis, idiopathic sympathetic nerve hyperactivity triggers excess sweating, most commonly of the axillae, palms, soles, or craniofacial regions . Hyperhidrosis occurs in children and adults, with ~4.8% of the US population (~15.3 million people) affected . In an online survey of US teens, ~17.1% experienced excessive sweating, with a mean onset age of 11 years .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In primary hyperhidrosis, idiopathic sympathetic nerve hyperactivity triggers excess sweating, most commonly of the axillae, palms, soles, or craniofacial regions . Hyperhidrosis occurs in children and adults, with ~4.8% of the US population (~15.3 million people) affected . In an online survey of US teens, ~17.1% experienced excessive sweating, with a mean onset age of 11 years .…”
Section: Introductionmentioning
confidence: 99%
“…1 Hyperhidrosis occurs in children and adults, with~4.8% of the US population (~15.3 million people) affected. 1,2 In an online survey of US teens,~17.1% experienced excessive sweating, with a mean onset age of 11 years. 3 The substantial negative impact of hyperhidrosis on quality of life has been well established [4][5][6][7] and equated as comparable to, or greater than, the impact of psoriasis or eczema.…”
Section: Introductionmentioning
confidence: 99%
“…Hyperhidrosis, which is a condition characterized by sweat production exceeding that which is necessary to maintain normal thermal homeostasis, has an estimated prevalence in the United States of 4.8% (;15.3 million people). 1,2 The adverse impact of hyperhidrosis on quality of life has been well documented, [2][3][4][5][6] and a recent case-control study found that anxiety and depression are more than 3.5 times more prevalent among patients with hyperhidrosis than among those without it. 7 Hyperhidrosis treatments have included nonsurgical and surgical options that generally work to block sweat from reaching the skin surface (eg, antiperspirants), inhibit neuronal transduction to sweat glands (eg, onabotulinum toxinA or oral anticholinergic drugs), or destroy the sweat glands (eg, thermal ablation or surgical removal) or work via unknown mechanisms (eg, iontophoresis).…”
mentioning
confidence: 99%
“…7 Hyperhidrosis treatments have included nonsurgical and surgical options that generally work to block sweat from reaching the skin surface (eg, antiperspirants), inhibit neuronal transduction to sweat glands (eg, onabotulinum toxinA or oral anticholinergic drugs), or destroy the sweat glands (eg, thermal ablation or surgical removal) or work via unknown mechanisms (eg, iontophoresis). 2,8,9 These treatments vary greatly with respect to effectiveness, invasiveness, and side effects and prior to 2018 only 2 had been approved by the US Food and Drug Administration (FDA) for axillary hyperhidrosis (onabotulinum toxin A and a microwave device for thermal ablation of sweat glands). Although treatment regimens may vary according to patient characteristics and symptom severity, 2 patients generally remain unsatisfied with the currently available treatment options.…”
mentioning
confidence: 99%
See 1 more Smart Citation